Lateral Preference and Inter-limb Asymmetry in Completing Technical Tasks During Official Professional Futsal Matches: The Role of Playing Position and Opponent Quality - Palucci Vieira, Luiz H.; Kalva-Filho, Carlos A.; Santinelli, Felipe B.; Clemente, Filipe M.; Cunha, Sergio A.; Schimidt, Caroline V.; Barbieri, Fabio A. (Frontiers in Psychology, 2021)
This study had a purpose of analyzing dominant and non-dominant limb performances (frequency of use and accuracy) during match-play technical actions with ball possession (receiving, passing and shooting a ball) in professional futsal and also check for the possible influence of playing position and opponent’s quality. We analyzed data pertaining to eight matches of the FIFA Futsal World Cup Thailand 2012TM in which 76 male professional senior futsal players participated (44 right-footed and 32 left-footed). In total, we coded 5,856 actions (2550 ball receptions, 3076 passes and 230 shoots). Our main findings were that (a) players used the dominant limb more frequently than the non-dominant limb for all actions considered (p < 0.001; effect size (ES) medium-to-large); (b) accuracy was generally greater when using the dominant limb, regardless of the opponent’s quality (p < 0.01; ES large) but (c) in shooting actions, pivots showed similar accuracy between dominant and non-dominant limbs (p = 0.51; ES small). To conclude, when completing technical actions with the ball in futsal, high-level players depended to a greater extent on the use of their dominant lower limb during official matches. Excepting a similarity detected between limbs on shooting performance of pivots, players from all positional roles generally showed a higher accuracy rate in receiving, passing and shooting a ball when using their dominant limb as compared to their non-dominant one during match-play and the limb usage and accuracy seemed to be independent of the opponents’ quality.